Bayesian Premium Estimators for NXLindley Model Under Different Loss Functions (Statistics, Optimization & Information Computing, 2025)
The conditional distribution of (X|θ) is regarded as the NXLindley distribution. This study is centered on the estimation of the Bayesian premium using the symmetric squared error loss function and the asymmetric Linex loss function, employing the extension of Jeffreys as non-informative priors and Gamma prior as informative priors. Owing to its complexity and lack of linearity, we rely on a numerical approximation for establishing the Bayesian premium. A simulation and comparison study with several sample sizes is presented.